A comparison of antigens bcl-2 and ki-67 expression alongside apoptosis between odontogenic keratocyts and amloblstomas - Seyed mohamad Razavi; Seyed Hasan Tabatabaei Ardakani (Isfahan University of Medical Sciences, 2009)
Introduction: Odontogenic Keratocyte is an evolutionary odontogenic cyst with an invasive nature and high recurrence rate. In this study, expression of bcl-2, the index for apoptosis inhibition was traced in OKCs via immunohistochemical assay. Expression of ki-62, the antigen indicating cellular proliferation was also checked similarly. The Tunel method was applied to look for apoptosis. The collected data were then compared to those of Amloblastomas to gain a better understanding of OKCs.Materials and Methods: This was a cross-sectional, analytic and retrospective study. Sixteen samples of OKCs alongside a similar number of paraffin embedded solid amloblastomas (SAB) already fixed in formalin were studied. The conventional Biotin-Streptavidin immunohistocheical assay was used to recognize through Tdt-Mediated dutp- biotin nick end TUNEL labeling. The collected data were then analyzed via independent and paired t- test on a computer using SPSS v11.5Results: Bcl-2 positive cells in the basal layer of OKCs(97.69% + 1.2) significantly outnumbered similar cells(53.01% + 18.57) in the peripheral layer of SABs.(P‹0.0001)The population of ki-67 positive cells in the suprabasal layer of OKCs(13.59+7%.47) was obviously greater than in any other layers. It was especially higher than in the peripheral layer of SABs.(7.38%+6.94). Although the population of ki-67 positive cells were larger in OKCs than in SABs, the difference did not prove significant.(P=0.211) TUNEL positive cells in the peripheral layer of OKCs (7.69%+ 2.6)was significantly higher than in the deeper layers of SABs(1.95%+ 0.38)Conclusion: The invasive nature and the high recurrence of OKCs compared to SABs seems to be due to the high proliferate activity of suprabasal cells rather than long cellular survival in the peripheral layers. Of course apoptosis in the superficial layers of OKCs seems to counteract the high proliferative activity of the deeper layers of amloblastomas. As a result, OKCs maintain the same epithelial thickness quite contrary to amloblastomas forming a solid tumoral mass.